Value-at-Risk with Application of DCC-GARCH Model - Tomas Meluzin; Marek Zinecker; Michal Bernard Pietrzak; Marcin Faldzinski; Adam P. Balcerzak (Institute of Economic Research (IER), 2016)
The article concentrates on modelling of volatility of capital markets and estimation of Value-at-Risk. The aim of the article is the description of volatility and interdependencies among three indices: WIG (Poland), DAX (Germany) and DJIA (United States). In order to measure the volatility and strength of interdependencies DCC-GARCH-In model was used, where an impact of the volatility of other markets is additionally taken into consideration during construction of the model. The conducted research for the years 2000-2012 confirmed the presence of interactions among selected capital markets. Next, the model DCC-GARCH-In was applied for evaluation of Value-at-Risk and the obtained measure was assessed with application of backtesting procedure. The results confirm that including volatility in the variance in DCC-GARCH-In model enables better assessment of VaR measure.
Keywords: G15; C58; 330; capital market; value-at-risk; backtesting; DCC-GARCH model; conditional variance